Patient Reported Impact of Symptoms in Spinal Muscular Atrophy (PRISM-SMA). (25th September 2018) - Mongiovi, Phillip; Dilek, Nuran; Garland, Connie; Hunter, Michael; Kissel, John T.; Luebbe, Elizabeth; McDermott, Michael P.; Johnson, Nicholas; Heatwole, Chad
Abstract : Objective: To determine the frequency and relative importance of symptoms experienced by adults with spinal muscular atrophy (SMA) and to identify factors that are associated with a higher burden of disease in this population. Methods: We conducted a cross-sectional study of 359 adults with SMA using the International SMA Patient Registry. Participants provided input regarding 20 symptomatic themes and 207 symptoms that potentially affect adults with SMA. Participants were asked about the relative importance of each symptom, and analysis was conducted to determine how age, sex, SMA type, education, mobility, and employment status relate to symptom prevalence. Results: Limitations with mobility or walking (98.6%) and the inability to do activities (98.6%) were the 2 themes with the highest prevalence in the study sample. Limitation with mobility or walking was the theme that was identified as having the greatest effect on the lives of adults with SMA. Employment status was associated with the prevalence of 4 of 20 themes and a reliance on an assistive device was associated with 7 of 20 themes. The prevalence of breathing difficulties, choking or swallowing difficulties, and communication difficulties differed among those with different SMA types. Conclusions: There are many symptomatic themes that affect the lives of adults with SMA. These themes vary in prevalence and relative importance in the adult SMA population.